2009
DOI: 10.1007/bf03194498
|View full text |Cite
|
Sign up to set email alerts
|

Volume sculpting based on geometric tools

Abstract: Abstract:The analysis of volumetric datasets is the main concern in many areas ranging from geophysics to biomedical sciences. The direct visualization of these data plays an important role in this scenario, and in spite of developments in volume visualization techniques, interacting with large datasets still demands research efforts due to perceptual and performance issues. There is a need of interactive sculpting tools which can provide an intuitive way to examine and explore inner parts of the datasets, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Huff et al [23], [24] reported the development of interactive, intuitive and easy-to-use sculpting tools, which specify regions within the volume to be discarded from rendering, thus allowing the inspection of the inner volume. Interactive rates were obtained for these sculpting tools by running special fragment programs on the graphics hardware.…”
Section: A Example Application Overviewmentioning
confidence: 99%
“…Huff et al [23], [24] reported the development of interactive, intuitive and easy-to-use sculpting tools, which specify regions within the volume to be discarded from rendering, thus allowing the inspection of the inner volume. Interactive rates were obtained for these sculpting tools by running special fragment programs on the graphics hardware.…”
Section: A Example Application Overviewmentioning
confidence: 99%
“…Many applications deal with volumetric data, which can be visualized either directly, using transfer functions that map data values to color and opacity values, or as surfaces that are extracted from the volume by some thresholding process. Both categories of visualization algorithms have been investigated in successive projects within our group as well as ways of interacting with volumes either carving or adding material as a sculptor [4]. Recent results allow interactive visualization of the volume interior displayed as an illustration (Fig.…”
Section: Interactive Volume Visualizationmentioning
confidence: 99%